CORAK DAN METODE PENAFSIRAN AL-QUR’AN - Sudirman Sudirman (El-QUDWAH, 2007)
The title of the research is The Koran Concept of Business Ethics (A Thematic Interpretation Study). The aim is to identify business ethics according to The Koran. This research is a library research. Therefore, to have a credible and capable, as well as valid data, the data gathering technique used is documentation, which was followed by data analysis using qualitative descriptive method, and then data interpretation. The sources of data are primary data that were taken from The Koran, and possibly from hadits (prophet Mohammed sayings). Meanwhile, the secondary data were taken from data written by the experts (The Koran and hadits were excluded) concerning the business ethics. The results of the research indicated that the Koran concept of business ethics is very comprehensive. The parameters used were not only matters of living in this world but also living in the world hereafter. According to the Koran, a successful business is a business that makes profit for the businessman in this perishable and limited world and the unlimited eternity hereafter. The formal legal business in Islam is of two fundamental principles, independence and justice. A well behavior and action in business, as in the business transaction reflects the same two principles plus the awareness of Allah existence, kindness and devotion motive.Keywords:The Koran, Interpretation Method, Development and Pattern of Thinking.